Effectiveness of Digital Self-Management Toward Fluid Restriction on Interdialytic Weight Gain Among Patients Undergoing Hemodialysis in Jakarta Islamic Hospital - Wahdaniyah, Wahdaniyah; Nursanti, Irna; Irawati, Diana; Natashia, Dhea; Resnayati, Yeti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Controlling interdialytic weight gain (IDWG) in hemodialysis (HD) patients requires a key component of fluid restriction. If IDWG rises, complications related to chronic renal failure may arise. Digital self-management improves fluid restriction in IDWG by empowering patients, increasing data monitoring, and simplifying communication with healthcare providers, perhaps leading to better hemodialysis patient outcomes. Objective: This study aims to determine the effectiveness of digital self-management toward fluid restriction on interdialytic weight gain among patients undergoing hemodialysis in Jakarta Islamic Hospital. Method: The study was quasi-experimental, using a pretest-posttest and control group. Convenience sampling was employed to select 25 intervention and 25 control group members. IDWG digital self-management can track fluid intake, weight, and symptoms, and patients can communicate openly with the health team. The data analysis used in this research is the T-test.  Results: In this study, respondents were categorized by gender, mean age, and duration of HD (months) in the intervention group (men 60%, 49.1 and 27.2) and control group (women 52%, 48.1 and 42.1). IDWG decreased in the intervention group, from 4.06 to 2.45, while it increased in the control group before 3.84 and after 4.34. The paired and independent t-tests demonstrated that digital-based fluid restriction management self-care interventions reduced IDWG with a p-value of 0.001. Conclusion: The digital self-management toward fluid restriction showed a promising impact on improving interdialytic weight gain among patients undergoing hemodialysis in Jakarta Islamic Hospital